Method for purifying lithium salts
Patent Information
- Application Number
- JP2022528583
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-19
- Filing Date
- 2020-11-17
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2040-11-17
Smart Images

Figure 0007645884000013 
Figure 0007645884000014 
Figure 0007645884000015
Abstract
Description
[Technical field]
[0001] The present invention is directed to a method for recovering high purity lithium hydroxide from lithium-containing sources that also contain fluoride ions, such sources may be geogenic, for example the lithium mineral lepidolite, or anthropogenic, such as waste lithium ion batteries that contain at least one transition metal selected from the group consisting of nickel, manganese and cobalt. [Background technology]
[0002] Lithium extraction typically involves calcining lepidolite mineral with limestone, and from a solution of material containing lithium hydroxide and lithium fluoride, most of the lithium fluoride can be removed after concentration and filtration, with the resulting filtrate still likely to contain small amounts of fluoride as determined by solution equilibrium.
[0003] A similar situation may arise in the recycling of lithium-ion batteries, where lithium and fluoride-containing solutions may also be obtained during the recycling process. The present method of purifying LiOH is particularly directed to the separation of lithium hydroxide from undesired impurities, such as fluoride salts, by extracting lithium from a raw blend of lithium hydroxide using a liquid that contains or consists of certain organic solvents, such as methanol.
[0004] Several methods have been described to lead from waste lithium battery material, e.g. whole discharged and shredded batteries or further dismantled and / or mechanically separated batteries, to a material consisting preferentially of one or more lithium salts, suggesting that such salts may be further used to prepare new lithium-ion batteries or electrode materials thereof. WO 2018 / 223193 describes the preparation of lithium by Li, after prior separation of Ni, Cu and Mn by ion exchange and Co by precipitation. 2 CO 3A method for precipitating lithium hydroxide as a precursor is described in CN107017443. A similar method is proposed in which the lithium hydroxide product is optionally directly solidified. Korean Patent Publication No. 10-1998691 proposes a method for obtaining a lithium precursor, e.g. LiOH, from an electrode material for a lithium ion battery. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2018 / 223193 [Patent Document 2] China Patent Application Publication No. 107017443 [Patent Document 3] Korean Patent No. 10-1998691 Summary of the Invention [Problem to be solved by the invention]
[0006] A problem that arises during the recovery of valuable components from battery scrap is the presence of impurities, especially fluorides, originating from the electrolyte or binder materials.
[0007] It has now been found that purification of raw lithium hydroxide containing LiF and / or salts of amphoteric elements can be efficiently accomplished by dissolving such material in a lower alcohol or a mixture of solvents based on lower alcohols. [Means for solving the problem]
[0008] The method thus relates to the purification of raw lithium hydroxide, which can typically be obtained from mining solutions or from materials including waste lithium ion batteries or components thereof, the method comprising: (A) providing crude lithium hydroxide containing fluoride as a solid; (B) combining the crude lithium hydroxide provided in step (A) with a lower alcohol. [Brief description of the drawings]
[0009] [Figure 1] X-ray powder diffractogram (Mo Ka) of the reduced mass from spent lithium ion batteries after heating / reduction treatment obtained in Example 1a and used in Example 2a, including reference diffractograms of graphite, cobalt, manganese(II) oxide, cobalt oxide and nickel. [Diagram 2] X-ray powder diffractogram (Mo Ka) of the reduced mass from spent lithium ion batteries after heating / reduction treatment obtained in Example 1a and used in Example 2a, including reference diffractograms of graphite, lithium aluminate and lithium carbonate. [Diagram 3] X-ray powder diffractogram (Cu Ka) of the reduced mass from spent lithium ion batteries after heating / reduction treatment obtained in Example 1a and used in Example 2a, including reference diffractograms of graphite, cobalt, manganese(II) oxide, cobalt oxide and nickel. [Figure 4] X-ray powder diffractogram (Cu Ka) of the reduced mass from spent lithium ion batteries after heating / reduction treatment obtained in Example 1a and used in Example 2a, including reference diffractograms of graphite, lithium aluminate and lithium carbonate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The crude lithium hydroxide may be provided in step (A) as a single phase solid or a mixture of solid phases. A liquid may be present, but in a preferred method, the crude lithium hydroxide is provided as a dry solid in the absence of a liquid phase. Since no purification is required in this step, the crude lithium hydroxide can be dried in a dryer, such as a paddle dryer, spray dryer, spin flash dryer, fluidized bed dryer, riser or rotary kiln. Depending on the drying temperature, lithium hydroxide monohydrate or lithium hydroxide anhydrous or any mixture of both is obtained and thus provided in this step (A). Nevertheless, the crude lithium hydroxide solid may still contain water in excess of the water of crystallization resulting from solvent residues, such as lithium hydroxide monohydrate, typically up to about 5% by total weight of the solid.
[0011] The crude lithium hydroxide provided in step (A) contains fluoride as an impurity, typically Lithium hydroxide monohydrate containing 100 ppm to 1.29% calcium, 0.1 to 1.29% fluorine, and 0.1 to 1.29% sodium; or and anhydrous lithium hydroxide containing 175 ppm to 2.26% calcium, 0.175 to 2.26% fluorine, and 0.175 to 2.26% sodium, all amounts being by weight of dry solids, and in important embodiments, the amount of fluoride is 500 ppm or more based on the total weight of the crude lithium hydroxide solids. The crude lithium hydroxide provided in step (A) often contains one or more further impurities from the group of alkali salts, aluminium salts, zinc salts, the sum of alkali, aluminium and zinc typically in an amount of 100-500 ppm or more, for example 500-5000 ppm, based on the total weight of the crude lithium hydroxide solids. In an exemplary process of the invention, greater than 90% by weight (% bw) of the crude lithium hydroxide solids provided in step (A) consists of anhydrous lithium hydroxide or lithium hydroxide monohydrate, or a mixture thereof.
[0012] The lower alcohol is generally selected from C1 to C4 alcohols or a mixture of such alcohols, for example methanol and / or ethanol. The lower alcohols added in this step (B) are typically technical products that may contain up to about 6% water by weight, and typically the lower alcohol product or the solvent mixture based on such alcohols consists of 93% or more by weight of lower alcohols. Thus, the lower alcohol product typically contains a lower alcohol purity of at least 93% by weight, preferably at least 95% by weight, more preferably at least 98% by weight and especially at least 99% by weight, the remainder in the product being mainly other alcohols and / or water, while other impurities, such as non-alcohol organic solvents, may be present up to 1% by weight of the lower alcohol product or the solvent mixture based on such alcohols. The lower alcohol is preferably methanol, ethanol or a mixture thereof.
[0013] The ratio of alcohol:LiOH applied in step (B) has a linear effect on the final fluoride content. This is due to the rather low solubility of LiF in lower alcohols. Thus, the amount of lower alcohol applied in step (B) should be sufficient to dissolve the crude lithium hydroxide resulting in a good overall lithium yield, but should be limited to avoid fluoride dissolution and high dilution effects. A typical method is, for example, to combine about 5-15 molar parts, in particular about 7-13 molar parts, of a lower alcohol, e.g., methanol, in step (B) with 1 molar part of the lithium provided in step (A).
[0014] In a typical process, the combined lithium hydroxide and lower alcohol of step (B) are subsequently mixed to obtain a suspension of solid particles in the lithium hydroxide solution. The resulting solution containing dissolved LiOH may then be separated from undissolved impurities by solid-liquid separation (step C), e.g., filtration, sedimentation, decantation, centrifugation, etc. In a preferred method, the solution of lithium hydroxide obtained in step (B) is subsequently (C) solid-liquid separation to obtain a clear solution; (D) optionally followed by the addition of water; and (F) Isolation of lithium hydroxide solid as anhydrous, or as a monohydrate, or as a mixture of anhydrous and monohydrate, or as a mixture of the monohydrate with water and / or a lower alcohol, or as a mixture of anhydrous and a lower alcohol. will be provided.
[0015] Further purification can be carried out by an additional step of aqueous crystallization, performed before step (A), for example by crystallization of the lithium hydroxide containing leachate, or after step (B), for example after removal of the solids by removal of the alcohol and addition of water followed by solid-liquid separation (step C). The solid lithium hydroxide thus purified may be recovered from the solution using known methods, such as crystallization, drowning-out crystallization by addition of less polar solvents, such as higher alcohols, ethers or hydrocarbons, drying, and the like.
[0016] In a particular variation of the preferred process, the methanolic solution of lithium hydroxide obtained in step (B) is subsequently (C) Solid-liquid separation to remove undissolved impurities, e.g. LiF, to obtain a clear solution; (D) optionally followed by the addition of water; (E) by removal of the solvent (E1) or by crystallization (E2) to immediately obtain purified lithium hydroxide, and (F) separation of the crystals from the liquid, if (E2) is performed; and (G) Drying of crystals In such a process, solid LiOH is obtained in step (E1) or (F) and (G) anhydrate, or as monohydrate, ... or as mixture of anhydrate and monohydrate, or as mixture of monohydrate with water and / or lower alcohol.
[0017] The lower alcohol used is advantageously recovered by distillation or evaporation and recycled in the process, but water can also be separated from the lower alcohol in which it is present, for example by collecting the solvent from step (E1) or the mother liquor separated in step (F), and reused in step (B). To avoid the content of higher alcoholates or alcohols (typically methylates or methanol), water can be added during the alcohol evaporation, preferably at the end of the evaporation (E1) or alternatively during the crystallization (E2).
[0018] It is a discovery of the present invention that the present process is particularly efficient and particularly low fluoride contents can be reached when steps (A), (B) and (C) of the process are carried out with only small amounts of water or in the absence of any water at all, and thus the crude lithium hydroxide solid provided in this step (A) advantageously contains less than 1 mole of water per mole of lithium, i.e. below the amount of water present in lithium hydroxide monohydrate. This can be done, for example, by providing the crude material for step (A) in the form of a mixture of monohydrate and anhydrous lithium hydroxide, in which no more than 90% or 80% or in particular 50% of the calculated total LiOH in step (A) is present as lithium hydroxide monohydrate besides anhydrous lithium hydroxide (pure LiOH×H 2(O contains 16.55 wt. % lithium and 42.9 wt. % water, while the anhydrous contains 28.99 wt. % lithium.) Therefore, the amount of water present in the methanol added during step (B) must be kept as low as possible, for example by using heavily dried methanol, typically well below the amount that would convert all the anhydrous provided in step (A) to the monohydrate. In a variant of this process, water is used only in less than stoichiometric amounts or not at all prior to step (C). Thus, water is preferably added in step (D) in an amount that reduces the formation of alcoholates, especially during the subsequent drying step, to less than 5 mol %, preferably less than 1 mol %, of the total lithium in the dried product. In one example of such a preferred process, for each mole of lithium provided in step (A), about 1 or more molar parts of water are added in step (D), typically 1-5 mol, preferably 1-3 mol, most preferably 1-2 mol.
[0019] Thus, in a preferred process, the crude lithium hydroxide solid provided in step (A) contains more than 50 mol % of lithium hydroxide in anhydrous form, and after step (C) (in step D) water is added in an amount of 1-5 mol per molar part of lithium, preferably 1-3 mol, most preferably 1-2 mol.
[0020] Typically, the solid lithium hydroxide product obtained according to the present invention (steps E, F and / or G) contains a certain amount of residual carbon compounds (total carbon [TC] or in particular non-purgeable organic carbon [NPOC] as described below). In particular the residual content of NPOC is typically in the range of 1-5000 ppm, in particular in the range of 1-3000 ppm, of the total mass of the solid product obtained by the above process. Such residual NPOC is determined as further explained below. Examples of NPOC are residues of lower alcohols, in particular methanol, used in this step (B) or elemental carbon (e.g. graphite is detected as NPOC) and small amounts of lithium alcoholates, e.g. LiOCH 3 may also be present but is preferably avoided due to handling and storage problems, especially when the amount of alcoholate in the product exceeds 5 mol % or even 1 mol % of lithium.
[0021] The solid lithium hydroxide product thus obtained typically contains at least 50% by weight LiOH, often with the presence of water, e.g. lithium hydroxide monohydrate.
[0022] Solid lithium hydroxide products containing 1-100 ppm of fluoride and 1-1000 ppm, especially 5-500 ppm of said lower alcohol, such as ethanol or especially methanol, respectively, based on the total weight of the solid product, are preferred.
[0023] The crude lithium hydroxide provided in step (A) is typically obtained from lithium ion battery scrap material, e.g., with impurity levels as described above.
[0024] Essentially, any solution containing lithium and fluoride ions in dissolved form can be used as the source of the crude lithium hydroxide solid in step (A), which can be obtained after removing at least a portion of the solvent, and in a typical process, the crude lithium hydroxide solid provided in step (A) is obtained by drying and / or crystallization, optionally after separation of the solid from the solution. The crude lithium hydroxide provided in step (A) can be obtained from leaching a material containing lithium hydroxide, or from chemical or electrochemical conversion of a suitable starting material. Thus, the starting material can also be a fluoride-containing lithium salt other than hydroxide (e.g. bicarbonate / carbonate, chloride, nitrate or sulfate). From such salts, the raw lithium hydroxide can be obtained, for example, by reaction with alkaline earth hydroxides or by electrolysis or electrodialysis or by calcination (lithium nitrate) and subsequent hydrolysis.
[0025] To obtain crude lithium hydroxide, the material obtained from battery scrap is typically subjected to subsequent steps of reduction, aqueous leaching, optionally in the presence of an alkaline earth hydroxide (preferably calcium hydroxide), separation of the solids and drying and / or crystallization.
[0026] Therefore, the present invention further relates to a method for recovering lithium from a material containing waste lithium ion batteries or parts thereof, the method comprising, prior to the steps (A) and (B), (a) providing a reduced particulate material comprising a transition metal compound and / or a transition metal, the transition metal being selected from the group consisting of Mn, Ni and Co, the particulate material further comprising a lithium salt and a fluoride salt, the particulate material optionally comprising calcium; (b) treating the material provided in step (a) with a polar solvent; (c) separating the solids from the liquid, optionally followed by washing the solid residue.
[0027] Typically, the lithium-containing transition metal oxide material is obtained after mechanically removing the casing, wiring or circuitry, and therefore typically consists mainly of cell materials.For safety reasons, such lithium-ion batteries are fully discharged, for example by immersion in a dry conductive bath, for example metal strips, otherwise short-circuits may occur that are a fire and explosion hazard.Such lithium-ion batteries can be disassembled, punched, crushed, for example in a hammer mill, or shredded, for example in an industrial shredder.
[0028] Before subjecting the material to the preliminary step (i), it may be advantageous to at least partially remove the electrolyte, in particular an electrolyte comprising an organic solvent or a mixture of organic solvents, for example by drying, for example under subatmospheric pressure at a temperature in the range of 50-250° C. The lithium-containing transition metal oxide material is preferably not exposed to high temperatures (in particular above 400° C.) under oxidizing conditions before it is subjected to this step (a).
[0029] In one embodiment of the present invention, the lithium-containing transition metal oxide material is from battery scrap. In a preferred embodiment of the present invention, the lithium-containing transition metal oxide material is from mechanically treated battery scrap, for example battery scrap treated in a hammer mill or industrial shredder.
[0030] The particulate material provided in step (a) typically comprises material obtained from waste lithium ion batteries after carrying out a preliminary step of heating to a temperature in the range of 80-900°C under inert or reducing conditions, this reduction being typically carried out after discharging, dismantling and / or shredding the lithium ion batteries. The reduction is advantageously carried out under conditions including the presence of carbon and a reducing gas selected from hydrogen and carbon monoxide. The temperature during such a reduction step is preferably in the range of 200-800°C, more preferably in the range of 350-500°C, in particular in the range of 350-450°C. In an important embodiment, the reduction is carried out in the presence of 35% by volume or more of hydrogen, preferably 50-100% by volume (normal conditions), the remainder, if present, being a non-oxidizing gas. In said embodiment of the invention, this reduction step has a duration in the range of 10 minutes to 30 hours, preferably in the range of 20 minutes to 8 hours, more preferably in the range of 30 minutes to 4 hours. Of particular technical interest are reduction steps with a duration of 20-90 minutes, in particular 30-60 minutes, preferably with the presence of hydrogen. The hydrogen concentration in the reducing atmosphere and the reaction time are interdependent. Usually, lower concentrations of hydrogen require longer reduction times and vice versa. In a further important embodiment, the reduction is carried out by heating in the initial presence of oxygen and carbon in a closed furnace with the formation of carbon monoxide. The lithium ion batteries used, and thus the particulate material provided in step (a), typically contain carbon, for example in the form of graphite.
[0031] In one embodiment, the reduction conditions, related to hydrogen and / or carbon monoxide concentration as well as temperature and duration, are selected such that at least a portion of the resulting lithium-containing transition metal oxide material contains para-magnetic, anti-ferro-magnetic, ferro- and / or ferri-magnetic components. The formation of ferro- or ferri-magnetic components resulting from at least partial reduction of the lithium-containing transition metal material is preferred. The extend of the reduction can vary in the range between 1 and 100% with respect to the nickel contained in the lithium-containing transition metal material, with a range of 80-100% being preferred.
[0032] Thus, the particulate material provided in step (a) comprises a transition metal compound and / or transition metal selected from the group consisting of Mn, Ni and / or Co, and further wherein at least a portion of said Ni and / or Co, if present, is in an oxidation state below +2, and wherein at least a portion of said Mn, if present, is manganese(II) oxide, in which the nickel and / or cobalt are typically at least partially present in the metallic state.
[0033] In the following, the particulate material of this embodiment prepared in step (a) and the material subjected to the preliminary reduction step are alternatively collectively referred to as a lithium-containing transition metal oxide material. Typically, such a lithium-containing transition metal oxide material is derived from a lithium-ion battery, and preferably contains fluorine in the range of 1 wt% to 8 wt% and / or phosphorus in the range of 0.2 wt% to 2 wt%, based on the weight of the lithium-containing transition metal oxide material.
[0034] As a result of reducing the particulate material prior to step (a) above, at least a portion of the Ni and / or Co, if present, is in an oxidation state less than +2, and at least a portion of the Mn, if present, is manganese (II) oxide. The transition metal compounds and / or transition metals Ni and / or Co in an oxidation state less than +2 contained in the particulate material provided in step (a) mostly contain Ni and / or Co in the metallic state detectable by powder X-ray diffraction (Cu-k-alpha-1 radiation). The lithium salts and fluoride salts contained in the particulate material provided in step (a) are typically LiOH, LiF, Li 2 O, Li 2 CO 3 , LiHCO 3 , lithium aluminates, lithium phosphates, mixed oxides of Li and one or more of Ni, Co, Mn, Fe, Al, Cu, and / or fluorides of Ni, Co, Mn, Fe, Al, Cu.
[0035] Intense heating, especially under oxidizing conditions and to a lesser extent under reducing atmospheres, can lead to the formation of insoluble species (e.g. LiMnO 2 It is generally preferred not to expose the lithium-containing transition metal oxide material to temperatures of 500° C. or higher, as this tends to increase the formation of . Accordingly, the particulate material provided in step (a) is preferably not exposed to temperatures of 400° C. or higher under oxidizing conditions before it is subjected to this step (a).
[0036] In one embodiment of the present invention, the material provided in step (a) is subjected to a dry solid-solid separation prior to step (b) to separate the transition metal-containing components.
[0037] In an exemplary embodiment of the invention, the lithium-containing transition metal oxide material provided in step (a) comprises copper, either as the metal or in the form of one or more of its compounds, in the range of 20 ppm to 10 wt. %, in particular in the range of 20 ppm to 3 wt. %.
[0038] In an exemplary embodiment of the invention, the lithium-containing transition metal oxide material provided in step (a) comprises aluminum in the range of 100 ppm to 15 wt. % either as the metal or in the form of one or more of its compounds.
[0039] In an exemplary embodiment of the invention, the lithium-containing transition metal oxide material provided in step (a) comprises iron in the range of 100 ppm to 5 wt. % as a metal or an alloy, or in the form of one or more of its compounds.
[0040] In an exemplary embodiment of the invention, the lithium-containing transition metal oxide material provided in step (a) comprises zinc in the range of 20 ppm to 2 wt. % as a metal or an alloy, or in the form of one or more of its compounds.
[0041] In an exemplary embodiment of the invention, the lithium-containing transition metal oxide material provided in step (a) comprises zirconium in the range of 20 ppm to 2 wt. % as a metal or an alloy, or in the form of one or more of its compounds.
[0042] In an exemplary embodiment of the present invention, the lithium-containing transition metal oxide material provided in step (a) comprises fluorine in the range of 1 wt.% to 8 wt.%, in particular in the range of 2 wt.% to 8 wt.%, calculated as the sum of organic fluorine bound in the polymer and inorganic fluoride in one or more of the inorganic fluorides.
[0043] In an exemplary embodiment of the present invention, the lithium-containing transition metal oxide material provided in step (a) comprises phosphorus in the range of 0.2% to 2% by weight, which may occur in one or more inorganic compounds.
[0044] Each of the above percentages is by weight of the dry material (i.e., the lithium-containing transition metal oxide material provided in step (a)).
[0045] The lithium-containing transition metal oxide material includes nickel and cobalt. Examples of lithium-containing transition metal oxide materials may be based on lithiated nickel cobalt manganese oxide ("NCM") or lithiated nickel cobalt aluminum oxide ("NCA"), or mixtures thereof.
[0046] The pretreatment of the battery scrap material and / or steps (a)-(c) can be carried out according to JP 2012-229481, whereby the waste batteries can be treated in one or more steps to bind the fluorine contained in the conductive electrolyte salt, usually LiPF6, and the binder polymer, usually polyvinylidene fluoride (PVDF). This can be achieved by treating the waste batteries with an aqueous calcium hydroxide (slaked lime) solution to hydrolyze the conductive salt and precipitate the fluoride as calcium fluoride. JP 2012-229481 discloses a method for recovering metals from used lithium-ion batteries, which includes a pre-soaking step followed by aqueous treatment with high temperature oxidation, reductive roasting, filtration, followed by carbonation to convert lithium hydroxide and recover lithium as carbonate. The present method does not require such carbonation.
[0047] The material provided in step (a) is typically milled prior to step (b) in order to deagglomerate the different solid particles from one another if they are somehow agglomerated, for example by residual binder polymer. Milling can be carried out under dry or wet conditions. Preferably, milling is carried out in an aqueous medium which is also used in the subsequent step (b). The particulate material provided in step (a), obtained from waste lithium ion batteries, in particular cell material thereof, is advantageously provided in the form of a dry powder, a wet powder or a suspension of particles in a liquid, the particles comprising typically having an average particle size D50 in the range of 1 μm to 2 mm, as detected according to ISO 13320 EN:2009-10.
[0048] The polar solvent used in step (b) and optionally in step (c) to wash the solid residue is typically selected from water, alcohols, ketones, esters, organic carbonates, polyethers, nitriles and mixtures thereof that can dissolve calcium hydroxide as well as or even better than water. Examples of such solvents are polyols such as glycols, glycerol or polyethylene glycols and mixtures thereof. The polar solvent may also be a protic solvent, such as water, alcohols and mixtures thereof. The aqueous medium is mainly water or a mixture of water and one or more alcohols. The polar solvent is preferably water or an aqueous solution, which generally contains cations of the above mentioned metals as well as further metals typically contained in battery scrap material or lithium minerals, e.g. Al, Zn, alkali, etc., as hydroxides and / or salts.
[0049] Step (b) is preferably carried out in the presence of an alkaline earth hydroxide. The alkaline earth hydroxide is generally selected from the hydroxides of Mg, Ca, Sr and Ba, with calcium hydroxide, barium hydroxide and mixtures thereof being preferred, with calcium hydroxide being most preferred. The alkaline earth hydroxide used in this step (b) may be used as such or may be added in the form of an oxide or a mixture of oxides and hydroxides, which may form an alkaline earth hydroxide when contacted with a polar solvent selected from the protic solvents mentioned above. This treatment is typically carried out by combining a quantity of alkaline earth hydroxide (AEH) with the particulate material (PM), which corresponds to at least 5% and typically not more than 100% of its weight, for example 50-1000 g AEH per kg PM, preferably 100-1000 g AEH per kg PM, more preferably 200-1000 g AEH per kg PM. The amount of polar solvent is typically selected to ensure miscibility of the components, for example, using an amount of polar solvent that is 2-20 times, preferably about 3-10 times, in excess of the combined weight amount of PM and EH.
[0050] Step (b) produces primarily a suspension of particulate material in a polar solvent, preferably with heating, typically carried out at temperatures in the range 60-200°C, preferably 70-150°C. If the boiling point of the polar solvent is exceeded, the process is carried out under pressure in order to keep the solvent or at least a fraction thereof in a liquid state. Of particular technical importance is the temperature range around the boiling point of water, i.e. about 70-150°C, where the process can be achieved using aqueous liquids or water at normal or slightly elevated pressures (e.g. up to 5 bar). Alternatively, this step (b) can be carried out applying higher temperatures and pressures, e.g. 150-300°C and 1.5-100 bar.
[0051] In one embodiment of the present invention, step (b) is carried out in a container protected from strong bases, for example, molybdenum and copper-rich steel alloys, nickel-based alloys, duplex stainless steels or glass-lined steel or enameled or titanium-coated steel. Further examples are polymer liners and polymer containers from base-resistant polymers, such as polyethylene, for example HDPE and UHMPE, fluorinated polyethylene, perfluoroalkoxyalkanes ("PFA"), polytetrafluoroethylene ("PTFE"), PVdF and FEP. FEP stands for fluorinated ethylene propylene polymer, which is a copolymer from tetrafluoroethylene and hexafluoropropylene.
[0052] The treatment is typically carried out using a mixing device, such as a stirrer, with a power supply typically up to 10 W per kg of suspension, for example 0.5-10 W / kg, or pumped to achieve good mixing and avoid settling of insoluble components. Shearing can be further improved by using baffles. Furthermore, the slurry obtained from step (b) can advantageously be subjected to a grinding treatment, for example in a ball mill or stirred ball mill, such grinding treatment can provide better access of the polar solvent to the particulate lithium-containing transition metal oxide material. The applied shearing and grinding devices are typically sufficiently corrosion resistant, and they may be manufactured from similar materials and coatings as described above for the vessels.
[0053] In one embodiment of the present invention, step (b) has a duration ranging from 20 minutes to 24 hours, preferably from 1 to 10 hours.
[0054] In one embodiment, step (b) is carried out at least twice to reach an optimum recovery of lithium hydroxide or lithium salt. Between each treatment, a solid-liquid separation is carried out. The resulting lithium salt solutions may be combined or treated separately to recover the solid lithium salt.
[0055] In one embodiment of the present invention, the polar solvent in step (b) is an aqueous medium, and the ratio of the aqueous medium to the material provided in step (a) is in the range of 1:1 to 99:1 by weight, preferably in the range of 5:1 to 20:1.
[0056] At the end of step (b), the pressure may be released, if applicable, and an aqueous solution containing LiOH is obtained.
[0057] In an important embodiment of the present invention, prior to steps (A) and (B), steps (a) to (c) are carried out as follows. (a) providing a particulate material comprising a transition metal compound and / or transition metal, the transition metal being selected from the group consisting of Mn, Ni and Co, and further wherein at least a portion of the Ni and / or Co, if present, is in an oxidation state less than +2, and at least a portion of the Mn, if present, is manganese (II) oxide, the particulate material further comprising a lithium salt and a fluoride salt, and optionally calcium, so long as the elemental ratio of calcium to fluorine is less than or equal to 1.7 or zero; (b) treating the material provided in step (a) with a polar solvent and an alkaline earth hydroxide; (c) Separating the solid from the liquid, optionally followed by washing the solid residue with a polar solvent, such as water.
[0058] The crude lithium hydroxide solid provided in this step (A) can be obtained after removal of the polar solvent or part of the solvent from the liquid obtained in step (c) or after further treatment as described below (optional steps d, e, e1, e2, e3).
[0059] In one embodiment of the present invention, the solid material obtained from step (c) is subjected to an additional step (d) of solid-solid separation. The material is advantageously milled prior to step (d) in order to liberate different solid particles from one another if they are somehow agglomerated, for example by residual binder polymer. Such milling is preferably carried out in a ball mill or a stirred ball mill.
[0060] In one embodiment of the present invention, step (d) is a wet solid-solid separation using an aqueous medium, preferably water, as the fluid. The ratio of the fluid medium to the solid material obtained in step (b) is in the range of 1:1 to 99:1 by weight, preferably in the range of 2:1 to 9:1.
[0061] From the wet solid-solid separation of step (d), two slurries are obtained, one containing the transition metal-containing solid material of interest and the other containing other components such as carbonaceous materials and polymers and, if applicable, also some inorganic compounds. By appropriate selection and, if necessary, combination of solid-solid separation steps, at least 60% of Ni and, if present, Co are obtained and concentrated in one fraction. Preferably, at least 80-99% of Ni and, if present, Co are separated.
[0062] In one embodiment of the invention, the liquid phase of the slurry fed to step (d) contains dissolved lithium. In this case, one or the other or both of the slurries resulting from the solid-solid separation in step (d) are subjected to solid-liquid separation to recover a lithium solution which is then further processed in step (e).
[0063] In step (e), the solution resulting from any of the previous steps containing lithium is treated to recover lithium in the form of a solid material, either as a hydroxide or a salt.
[0064] In one embodiment of the present invention, the Li salt, in particular LiOH, is recovered by evaporation of the water contained in the solution (e1). To produce the Li salt of the desired high purity, this evaporation can be carried out in two successive steps (e2 and e3), with a solid-liquid separation between steps e2 and e3 to remove undissolved solids. In step e3, the solution is dried or lithium hydroxide is obtained by crystallization or drown-out crystallization, the latter by adding higher alcohols or other components that are less polar but sufficiently miscible with water, such as ethers. In a preferred embodiment, steps (e), (e1), (e2) and (e3) are carried out in an inert atmosphere, for example under nitrogen or argon.
[0065] The two successive steps may include: First, the Li-containing solution from any of the previous steps is concentrated to a level just below the solubility limit of LiOH, typically the Li concentration is at least 5% lower than the corresponding saturated concentration of LiOH. This step involves the solid formation (e.g., crystallization) of impurities that have a lower solubility than LiOH, potential impurities include Ca(OH) 2 , CaF 2 , CaCO 3 , LiF. These are separated by solid-liquid separation, for example by filtration or centrifugation or a kind of settling and decantation. A depth filter is preferably applied since the amount of solid separated is small. If LiF precipitates in this first concentration step (e2), it is preferred to re-feed the solid material to step (b). The filtrate obtained from the solid-liquid separation after one of the concentration steps, i.e. the concentrated LiOH solution, is then used in the next evaporation step. High-quality LiOH can be obtained by evaporation of the residual water and solid formation of LiOH. In the case of crystallization, the crystals are again separated from the residual mother liquor by solid-liquid separation and optionally washed.
[0066] For all the above solidification steps, subsequent drying of the solid is advantageous to obtain the crude lithium hydroxide solid of step (A). Drying below 60° C. or above and under humid conditions results in LiOH monohydrate or else at least partially water-free LiOH.
[0067] If the filtrate obtained after step (c) is dried by total evaporation of a polar solvent, e.g. water, according to the described step (e1), a crude LiOH solid useful for the present step (A) may be obtained, which upon drying has a purity in the range of 90-99 wt%, typically about 98 wt%, and may contain a spectrum of impurities characteristic of the above-mentioned methods, as well as carbon-based impurities (typically <0.5 wt%).
[0068] With reference to the LiOH monohydrate thus obtained, the characteristic impurities are typically calcium, fluorine and sodium, the typical amounts of which in this LiOH monohydrate are as follows: Ca:100ppm~1.29wt% F:0.1~1.29wt% Na:0.1~1.29wt% Furthermore, depending on the composition of the starting material, significant amounts of zinc, aluminum, potassium and chlorine may be present. In these cases, their characteristic amounts in the LiOH monohydrate obtained after step (e1) are often within the following ranges: Zn:20ppm~1.29wt% Al:50ppm~1.29wt% K: 0.1~1.29% by weight Cl:0.1~1.29wt%
[0069] Depending on the drying conditions, anhydrous LiOH is obtained instead of the monohydrate, in which case the above-mentioned characteristic amounts of impurities associated with the monohydrate are 1.75 times (corresponding to the molar weight of the monohydrate divided by the molar weight of the anhydrous one) higher, respectively, than in 100% water-free LiOH. All steps including steps (b), (c), (d) and (e) are preferably carried out under an inert atmosphere, such as nitrogen, argon or CO. 2 The test is carried out in free air.
[0070] An exemplary embodiment can be described as follows. A residue obtained from battery scrap material containing lithium, fluoride and metallic cobalt and / or nickel is taken (step a) and stirred with water to which is added calcium hydroxide in an amount sufficient to bind all the fluoride contained in the material (step b), and the slurry is filtered (step c) to separate undissolved solids (e.g. cobalt and / or nickel metal, calcium fluoride, carbon). The leachate contains most of the lithium contained in the feed material dissolved as LiOH (the main lithium salt), where it is concentrated by evaporating the water to a LiOH concentration low enough that LiOH does not precipitate (step e2, i.e., less than 12 g LiOH / 100 g water), and the remaining precipitated less soluble material is separated.
[0071] Traces of metal cations, for example in the solutions obtained in steps b, c and / or e2, can be removed by various techniques according to the state of the art. Typical techniques are: i) a sulfide source, e.g., Na 2 S, NaHS, Li 2 S, LiHS or H 2 S, the latter two being preferred or upon addition of a mixture of at least two of the aforementioned sulfide sources, precipitation and subsequent separation of insoluble metal sulfides in step c or e2. ii) crystallization in aqueous solution after either step c or e2, either in the form of a one-step crystallization or in the form of two or more steps or successive fractional crystallization. Crystallization is preferred in the presence of highly soluble impurities, such as Na or K from NaOH, NaCl, KOH or KCl; besides these cations, even the chloride content can be significantly reduced by crystallization in aqueous solution. iii) Solvent extraction after either step c or e2. The precipitate is finally separated by solid-liquid separation, for example by filtration.
[0072] The lithium hydroxide containing liquid, which may result from either of steps c or e2 above, with or without any of the purification steps (i)-(iii), is finally converted to crude solid lithium hydroxide solid, either by evaporating the liquid to dryness or by crystallization or drown-out crystallization.
[0073] The solid residue of crude lithium hydroxide thus provided in step A is then treated with a lower alcohol, e.g. methanol (step B), in an amount to dissolve any LiOH contained in the solid residue; in a typical process of the invention, the concentration of LiOH in the thus obtained methanol solution is equal to or less than 9 g LiOH per 100 g of solution. This solution is filtered from any insoluble residues, such as residual salts based on fluorides, aluminates or zincates (step C). The methanolic LiOH filtrate is then concentrated to solidify the LiOH. The resulting LiOH can be dried to completely evaporate the methanol. It can be recrystallized from water to give hydrated lithium hydroxide, e.g., LiOH×H 2O or crystallization can be carried out directly in methanol / water mixtures. In one embodiment, solid lithium hydroxide is obtained by drown-out crystallization from a methanolic solution by addition of higher alcohols, ethers and / or hydrocarbons. The obtained lithium hydroxide is also of high purity, especially with respect to fluoride ion impurities and salts of amphoteric elements such as Al, Zn.
[0074] For example, the residue obtained from fluoride-containing battery scrap material prepared in step a is suspended in water and stirred with calcium hydroxide (or calcium oxide, which forms calcium hydroxide in water) at a solid content of 5-30% by weight and a molar ratio of Ca:Li ranging from about 1:3 to 1:1, typically for a period ranging from 1 hour to 8 hours, for example under reflux (step b, typically at normal pressure). After cooling to room temperature, the slurry is filtered (step c). The leachate is concentrated by evaporating the water (step e2) until the LiOH concentration is slightly below 12 g LiOH / 100 g water. Optionally, Li 2 S and / or H 2 S is added. The precipitate is finally separated by filtration. The remaining liquid is evaporated to dryness (step e3). The residue thus prepared (step A) is treated with methanol (step B) to obtain a LiOH concentration in methanol up to 9% by weight. The solution is filtered from any insoluble residues (step C). The methanolic LiOH filtrate is concentrated to crystallize high purity LiOH.
[0075] In a further embodiment, the slurry obtained from the aqueous leaching of step b in the previous example may be treated with sulfide and then evaporated to dryness (step e3) and subsequently redissolved in methanol (step B), thereby avoiding multiple filtration steps. The methanolic slurry is then filtered (step C) and pure LiOH with low fluoride content is isolated from the filtrate.
[0076] In the context of the present invention, the content of impurities is often based on lithium hydroxide anhydrous or lithium hydroxide monohydrate. 10 ppm of impurities in lithium hydroxide monohydrate corresponds to 17.5 ppm of impurities in lithium hydroxide anhydrous. The same level of impurities may be related to the lithium content useful in the case of anhydrous / monohydrate mixtures, where 10 ppm of impurities in lithium hydroxide monohydrate and 17.5 ppm of impurities in lithium hydroxide anhydrous corresponds to 60.4 ppm of impurities based on Li content.
[0077] Show me how Particle size distribution measurements including the determination of D50 are performed according to ISO 13320 EN:2009-10.
[0078] Elemental analysis of lithium, calcium and manganese (performed to determine, inter alia, the Li, Ca, Mn content of the particulate material provided in step (a): The reagents were deionized water, hydrochloric acid (36%), K 2 CO 3 -Na 2 CO 3 Mixture (dry), Na 2 B 4 O 7 (dry), hydrochloric acid 50% by volume (1:1 mixture of deionized water and hydrochloric acid (36%)), and all reagents are PA grade.
[0079] Elemental analysis of fluorine and fluoride is carried out according to the standardized method: DIN EN 14582:2016-12 for sample preparation (waste samples) for overall fluorine content determination. The detection method is ion-selective electrode measurement. DIN 38405-D4-2:1985-07 (water samples; decomposition of inorganic solids followed by acid-supported distillation and determination of fluoride using an ion-selective electrode).
[0080] Determination of carbon and alcohol content Carbon: In addition to organic carbon, samples may contain ions of carbon dioxide or carbonate. Depending on the species of interest, the following methods are applied:
[0081] Total Carbon (TC): A typical analysis of total carbon measures both the total organic carbon (TOC) present and the complementary total inorganic carbon (TIC), the latter representing the amount of non-organic carbon such as carbon in carbonate minerals. This is done by combustion in an oxygen-containing atmosphere. A description of this method is part of DIN EN 15936:2012-11 (Verfahren A).
[0082] TOC can be determined indirectly (a) and directly (b). a) TOC is calculated by subtracting inorganic carbon from total carbon (TC) and is described in DIN EN 15936:2012-11 (Verfahren A). b) Another common variant of TOC analysis involves first removing the TIC portion and then measuring the remaining carbon. This method involves purging the acidified sample with carbon-free air or nitrogen prior to measurement and is more correctly called non-volatile organic carbon (NPOC) since the volatile organics are also purged. NPOC is determined by purging the acidified sample with carbon-free air or nitrogen prior to measurement, followed by combustion in an oxygen-containing atmosphere (DIN EN 15936:2012-11, B).
[0083] Lower alcohols, e.g. methanol or ethanol, are identified and quantified by GC-MS (Gas Chromatography + Mass Spectrometry) headspace techniques (compliant with ISO 17943:2016) after separation of the lower alcohol from the LiOH matrix in a suitable solvent, such as water or aqueous hydrochloric acid.
[0084] Other metal impurities and phosphorus are similarly determined by elemental analysis using ICP-OES (Inductively Coupled Plasma-Optical Emission Spectroscopy) or ICP-MS (Inductively Coupled Plasma-Mass Spectroscopy). Total carbon is determined after combustion with a thermal conductivity detector.
[0085] The phase composition of the solid (including the identification of manganese(II) oxide and Ni and Co (typically metallic) in oxidation states less than +2 in the particulate material provided in step (a)) is determined using powder X-ray diffraction (PXRD), which is carried out as follows: The sample is ground into a fine powder and packed into the sample holder. It uses two devices, each of which uses a specific source of radiation. (1) Measurements applying Cu radiation: The equipment used is a Bruker D8 Advance Series 2 with an autosampling unit. First side: Cu anode, beam divergence aperture 0.1°, with ASS. Second side: Ni 0.5mm with scattered beam aperture 8mm, Solar 4°, Lynx-Eye (aperture 3°). (2) Measurements applying Mo radiation: the equipment used is a Bruker D8 Discover A25 with an autosampling unit. First side: Mo anode with a Johansson monochromator (Mo-K-Alpha 1) with axial solar 2.5°. Second side: ASS, solar 2.5°, Lynx-Eye XE detector (aperture 3.77°). References are used to identify matches with the obtained reflection pattern. All relevant phases are well known in the literature and are used with reference to the following references to calculate the theoretical diffraction pattern (see position and intensity of reflections in Table 1 below). a)Co x Ni 1-x ;space group FM-3m; x=0.5: Taylor et al., J. Inst. Met. (1950) 77, 585-594. x=0: Buschow et al., J. Magn. Magn. Mater. 1983, 38, 1-22. b)Co;space group P6 3 / mmc; Buschow et al., J. Magn. Magn. Mater. 1983, 38, 1-22. c) Li 2 CO 3, space group C2 / c; J. Alloys Compd. (2011), 509, 7915-7921 d) LiAlO 2 , space group R-3m; Marezio et al., J. Chem. Phys. (1966) 44, 3143-3145. e) MnO, space group Fm-3m, Locmelis et al., Z. Anorg. Allg. Chem. 1999, 625, 1573.
[0086] [Table 1]
[0087] If characteristic reflections overlap with those of different crystalline phases (especially graphite, which occupies the largest fraction of the sample), additional measurements using an alternative radiation source (e.g. Mo K alpha instead of Cu K alpha) are performed.
[0088] Short description: Steps A and B indicate required steps of the method; other steps described are optional and may be advantageous in the context described, e.g., steps identified with capital letters (mainly downstream) and steps identified with lower case letters (mainly upstream). In the context of the present invention, normal pressure means 1 atmosphere or 1013 mbar. "Normal conditions" means normal pressure and 20°C. Nl stands for normal liters, liters at normal conditions (1 atmosphere, 20°C). PFA stands for perfluoroalkoxy polymer, MeOH stands for methanol and EtOH stands for ethanol. Percentage or ppm refers to % or ppm by weight, and "in vacuum" refers to a reduced pressure in the range of 20-50 mbar, respectively, unless otherwise defined. The expressions % by weight (% bw) and wt% can be used interchangeably, with "wppm" standing for parts per million by weight and c standing for concentration. Wherever mentioned, the terms "room temperature" and "ambient temperature" refer to a temperature between 18°C and 25°C. XRD refers to powder X-ray examination (radiation is typically 154 pm Cu k-alpha 1 radiation or 71 pm Mo k-alpha 1, as indicated). EXAMPLES
[0089] The invention is further illustrated by the following examples, in which the LiOH content is calculated based on the analytically determined Li content, and the water content by weight can be estimated by subtracting the calculated LiOH content from 100%.
[0090] [Example 1] Synthetic extract samples 78.8 g of spent cathode active material containing similar molar amounts of nickel, cobalt, and manganese, with an approximate formula of Li(Ni 0.34 Co 0.33 Mn 0.33 )O 2 , Organic carbon in the form of graphite and soot 62.2 Organic electrolyte mixture (LiPF 6 (including) 47.0g 7.4 g of polyvinylidene fluoride as a binder, Aluminum powder 2.4g, Iron powder 0.2g, Copper metal 2.0g Simulated used battery scrap in the amount of 200g including are placed in a 500 mL quartz round-bottom flask and attached to a rotary evaporator in such a way that the flask is placed in a furnace. Within 4.5 hours, the rotary flask is heated to 800 °C over 2 hours under a flow of argon (20 l / h), kept at this temperature for 1 hour under a flow of dry air (20 l / h) and then cooled to ambient temperature. 2 CO 3 A quantity of 173.3 g of heat-treated material is obtained having a phase composition of LiF and graphite.
[0091] [Example 1a] Provision of reduced mass from waste lithium-ion batteries Mechanically treated battery scrap in an amount of about 1 tonne, containing spent cathode active material including nickel, cobalt and manganese, organic carbon in the form of graphite and soot, and residual electrolyte and further impurities including inter alia fluorine compounds, phosphorus and calcium, is treated according to the method described in Jia Li et al., Journal of Hazardous Materials 302 (2016) 97-104 to obtain an equivalent mass, except that the atmosphere in the torrefaction system is air, where oxygen reacts with the carbon in the battery scrap to form carbon monoxide, and the treatment temperature is 800°C.
[0092] After reacting and cooling to ambient temperature, the heat-treated material is recovered from the furnace and mechanically processed to obtain particulate material that is analyzed by X-ray powder diffraction (Figures 1 and 2: Mo Ka radiation, Figures 3 and 4: Cu Ka radiation), elemental analysis (Table 2), and particle size distribution (Table 3).
[0093] The Li content is 3.6 wt.% and serves as a benchmark for all further leaching examples (see below). The fluorine is represented mainly as inorganic fluoride (88%). The particle size is well below 1 mm, giving a D50 of 17.36 μm.
[0094] The obtained XRD patterns were x Ni 1-x, x=0~0.6), Co, Li 2 CO 3 and LiAlO 2 Comparing with the calculated reference pattern of (see reference pattern in Table 1), it can be concluded that Ni exists only as a metallic phase, either as pure Ni or as an alloy in combination with Co. For clarity, this result is confirmed by applying two different radiation sources. The presence of metallic nickel is supported by the qualitative observation that the whole sample shows a typical ferromagnetic behavior when in contact with a permanent magnet material. As a lithium salt, Li 2 CO 3 and LiAlO 2 is clearly identified by its characteristic diffraction pattern.
[0095] The composition of the obtained black powder (PM) is shown in Table 2.
[0096] [Table 2]
[0097] [Table 3]
[0098] [Example 2] The raw lithium hydroxide product in water can be obtained from the materials prepared in Example 1 or Example 1a according to the method proposed in Korean Patent Registration No. 101998691.
[0099] [Example 2a] Ca(OH) 2 Leaching by A 5 g amount of the above reduced battery scrap material (obtained as shown in Example 1a) was loaded into a PFA flask, and solid Ca(OH) 2 200 g of water are added with stirring and the whole mixture is refluxed for 4 hours. After 4 hours, the solids are filtered off and a filtrate sample is taken and analyzed for Li, F, carbonate, OH and Ca. The results are summarized in Table 4 below.
[0100] [Table 4]
[0101] [Example 3] Solid LiOH from leached lithium filtrate and subsequent recrystallization in methanol. Concentrated aqueous solution: The filtrate obtained from the process according to Example 2a is further treated according to steps (e2) and (e3) above to obtain solid LiOH as monohydrate. 1 L of the filtrate containing 0.21% by weight of lithium is concentrated 11 times by evaporation (40° C., 42 mbar), which is accompanied by the precipitation of finely distributed white crystals. The precipitate is filtered. Preparation of crude solid LiOH: The remaining solution is dried at 40° C. and a constant flow of nitrogen is applied for 24 hours. XRD shows that Li 2 CO 3 The resulting LiOH monohydrate with a trace impurity of Li 2 CO 3 This is due to contact with air during almost all process steps. Table 5 (Error! Reference source not found.) (middle column) shows the 2 The elemental analysis is based on 0 and includes all impurities analyzed. This fraction was prepared by distilling crude LiOH×H 2 Classify as O. Combination with lower alcohols: This crude LiOH×H 2 3 g of O is dissolved in 20 g of methanol at room temperature. The remaining insoluble solids are filtered and 4.5 g of water is added to the clear solution. The liquid phase is then slowly evaporated to give LiOH×H 2 White crystals of LiOH×H2O are obtained. The analytical results of this purified product are also shown in Table 5 (right column). 2 It is based on O.
[0102] [Table 5]
[0103] The results show that fluoride impurities and amphoteric elements Al and Zn are efficiently removed.
[0104] [Example 4] Solid LiOH from leached lithium filtrate by fractional crystallization followed by recrystallization in methanol Example 3 is repeated, applying fractional crystallization in the first step. 1 L of the filtrate, containing 0.21% by weight of lithium, is concentrated 11 times by evaporation (40° C., 42 mbar), which is accompanied by the precipitation of finely distributed white crystals. This precipitate is filtered off and the remaining solution is dried stepwise, applying 40° C. and 42 mbar. After a further 2-fold concentration, the first solid fraction is filtered off. The remaining mixture is concentrated again 2-fold and a second fraction is isolated. Tables 6 and 7 show the results of the LiOH×H 2 The elemental analysis of both fractions, including all the impurities analyzed, is shown relative to 100. These fractions were analyzed by addition of solid LiOH×H 2 Classified as O (middle column). Both fractions are subsequently recrystallized in methanol. Each time, the first or second fraction is recrystallized in solid LiOH×H 2 2 g of O is dissolved in 13 g of methanol. The remaining insoluble solids are filtered off and 3 g of water is added to the clear filtrate. The liquid phase is then slowly evaporated to give LiOH×H 2 White crystals of O are obtained. The analytical results of the purified product are shown in Tables 6 and 7 (right column).
[0105] [Table 6]
[0106] [Table 7]
[0107] This combination of fractional crystallization and recrystallization in methanol produces high purity lithium hydroxide.
[0108] [Example 5] Mainly monohydrate (LiOH×H 2 Recrystallization in MeOH starting from LiOH (as O) About 24 g of crude solid lithium hydroxide obtained according to Example 3 (mainly comprising the monohydrate with 18.2% by weight of Li, corresponding to 62.8% by weight of LiOH, about 37.2% by weight of water, c(F)=0.32% by weight) are added to methanol (m(MeOH) as shown in Table 8 below). The solution is stirred at ambient temperature for 16 hours. A cloudy solution is obtained, which is then filtered. The filtrate is dried in vacuum at 40° C. for 12 hours. The amount of product obtained [m(product) / g], the lithium yield and the residual fluoride impurities are summarized in the table below.
[0109] [Table 8]
[0110] The applied MeOH / LiOH ratio has a linear effect on the final fluoride content. This is due to the rather low solubility of LiF in MeOH. Therefore, applying large amounts of MeOH is not desirable. On the other hand, an increase in the MeOH content is beneficial for the overall lithium yield.
[0111] [Example 6] Recrystallization in MeOH starting from anhydrous-predominant LiOH The sequence of steps in the method is: 1) dissolution of solid LiOH in MeOH; 2) filtration to remove LiF; 3) addition of water; 4) drying. 9.9 g of crude solid lithium hydroxide (mainly anhydrous LiOH (c(Li)=23.9% by weight, c(F)=0.3% by weight, NPOC 1739 ppm by weight, water content about 17.6% by weight), obtained analogously to example 3 but dried at 110° C., are added to 115 g of methanol. The solution is stirred for 2 hours at ambient temperature. A cloudy solution is obtained which is then filtered. 8.75 g of water are slowly added to the filtrate. The filtrate is then dried at 70° C. and 200 mbar for 45 minutes, cooled to 45° C. at 100 mbar and finally dried at 40° C. and 40 mbar for 3.5 hours. 11.6 g of product are obtained (lithium NPOC content = 96.1%). Comparison of NPOC and MeOH content (3050 ppm by weight) gives an estimate of residual carbon not related to methanol. To reduce the MeOH content, the product is redissolved in water and dried again at 70°C for 1 hour. Analysis of the crude solid extract material and the dried solid product are summarized in Table 9. Assuming a constant carbon content not present as methanol after this recrystallization in water, the reduction in NPOC content is calculated as a loss of methanol. This estimate leads to 913 ppm of methanol in the product after redissolution and redrying, which is equivalent to the ideal LiOH x H 2 This corresponds to 521 ppm of methanol in O.
[0112] [Table 9]
[0113] This example represents the most preferred processing method since it achieves very efficient F depletion and good yields by keeping the moisture content as low as possible prior to separating the undesirable LiF impurity.
[0114] [Example 7] Recrystallization in MeOH starting from anhydrous LiOH, no water added Analogous to example 6, 22.8 g of crude solid lithium hydroxide obtained in the dried state at 110° C. (mainly containing anhydrous LiOH (c(Li)=27.8% by weight, corresponding to 95.9% by weight of LiOH and 4.1% by weight of water, c(F)=0.37% by weight)) are added to 296 g of methanol. The solution is stirred for 2.5 hours at ambient temperature. A cloudy solution is obtained, which is then filtered. The filtrate is then dried in vacuum at 40° C. for 12 hours. 25.5 g of product are obtained (lithium yield=90.0%). The analysis of the dried solid product is summarized in table 10.
[0115] [Table 10]
[0116] This example is less preferred because the product contains lithium methoxide, which is self-igniting, but F depletion is nevertheless as effective as in Example 6, since the water content is as low as possible prior to separating out the undesirable LiF impurity.
[0117] [Example 8] Recrystallization in MeOH, addition of water at early stage The sequence of steps in the method is: 1) dissolution of solid LiOH in MeOH; 2) addition of water; 3) filtration to remove LiF; 4) drying. 9.95 g of crude solid lithium hydroxide (c(Li)=23.9% by weight, corresponding to 82.4% by weight of LiOH and 17.6% by weight of water, c(F)=0.3% by weight) obtained analogously to Example 3 are added to 116 g of methanol. The solution is stirred for 2 hours at ambient temperature. 8.55 g of water are slowly added to the cloudy solution, which is then filtered. The filtrate is dried for 1 hour at 70° C. and 200 mbar, cooled to 45° C. at 100 mbar and finally dried for 4 hours at 45° C. and 45 mbar. 10.8 g of product are obtained containing 21.3% by weight of Li and 0.012% by weight of F (lithium yield=96.7%).
[0118] This example is less preferred than Example 6 because water is added prior to separating the unwanted LiF. This additional water can dissolve LiF. Therefore, F depletion is not as effective as described in the previous example.
[0119] [Example 9] Large-scale recrystallization starting from anhydrous-predominant LiOH 6.4 kg of concentrated aqueous lithium hydroxide solution (6.2% by weight), obtained as described in Example 3, are dried in a 0.77 l kneader dryer. The reactor is heated to 120-135°C and the product temperature is 100-105°C at 950 mbar. The solution is added in portions of 100 ml. The reactor is purged with 10 Nl / h of nitrogen during the entire process. The wall temperature rises to 140-155°C after 15 hours and is finally adjusted to 130-140°C for 1 hour. The product is then cooled to room temperature. During the process, the reactor is filled to 45-80% of its maximum capacity. 191 g of crude solid LiOH, mainly containing anhydrous lithium hydroxide, are obtained (c(Li)=27.8% by weight, which corresponds to 95.9% by weight of LiOH and 4.1% by weight of water, c(F)=0.33% by weight). 60 g of this free-flowing and crystalline powder is dissolved in 800 g of methanol and stirred for 16 hours. The mixture is filtered and 100 ml of methanol is added to the filtrate. The filtrate is dried at 70° C. and 200 mbar for 1 hour, cooled to 45° C. at 100 mbar and finally dried at 45° C. and 45 mbar for 4 hours. The analysis of the dried solid product is summarized in Table 11.
[0120] [Table 11]
[0121] Comparative Example A: Drowning Crystallization Using MeOH Drowning crystallization with methanol is carried out to remove impurities from the solution. Solid crude LiOH×H recycled from the black mass as described in Example 3 above was used. 2The crude LiOH×H is treated as follows: 2 3 g of O are dissolved in water (20.48 g, c(Li)=15.21 wt%) and stirred at ambient temperature for about 3 hours, adding methanol dropwise until the formation of a solid is visible. A total of 13.58 g of methanol is added. The suspension is then filtered and the clear filtrate is thoroughly dried. The dried solid residue is analyzed by elemental analysis, which shows a lithium content of 25.7 wt% and a fluoride content of 0.20 wt%, which corresponds to the stoichiometrically ideal LiOH×H with 1288 ppm fluoride. 2 Equivalent to O. Compared to the above examples, this comparative example applying drowning crystallization clearly highlights the less efficient fluoride removal that does not result in the preferred fluoride content obtained according to the present invention, which is in agreement with the above examples showing that the amount of LiF increases with increasing moisture content.
[0122] Comparative Example B: Drowning Crystallization Using Ethanol Drowning crystallization is carried out using ethanol as an antisolvent for crystallizing LiOH, as proposed for example by ME Taboada et al., Chem. Eng. Res. and Design 85, 1325 (2007). The concentrated, nearly saturated LiOH solution described in Example 3 (sources) above contains: Lithium = 2.9 wt% (equivalent to 10.0 wt% LiOH) Fluoride = 0.026 wt% (0.15 wt% LiOH × H 2 O)
[0123] i) In a first experiment, 40 g of ethanol is added to 100 g of this LiOH solution in the form of 70% (wt%) ethanol / water. After adding 35 g of EtOH, white crystals of LiOH are observed.
[0124] ii) In the second experiment, 40 g of a liquid consisting of 90% by weight ethanol and 10% by weight water is added to 100 g of this LiOH solution. After adding 19 g of EtOH, white crystals of LiOH are observed.
[0125] Mixtures (i) and (ii) are each stirred for 15 minutes. The precipitated salts are then filtered, dried (30 mbar and 40° C. for 3 hours) and analyzed for fluoride and lithium content. Pure LiOH×H 2 Fluoride content relative to pure LiOH*H 2 Calculate (pure LiOH × H 2 (O contains 16.55 wt. % Li). The results are summarized in the table below.
[0126] [Table 12]
[0127] Drowning crystallization with ethanol leads to a slight enrichment of fluoride in the precipitated LiOH, rather than a reduction of fluoride.
[0128] The project leading to this application has received funding from the Bundesministerium fur Wirtschaft und Energie (DE; FKZ:16BZF101A), and the applicant is responsible for all disclosures contained herein. The present invention includes the following aspects. [Section 1] A method for purifying lithium hydroxide from a material that typically comprises waste lithium ion batteries or components thereof, comprising the steps of: (A) providing crude lithium hydroxide containing fluoride as a solid; (B) combining the crude lithium hydroxide provided in step (A) with a lower alcohol, such as methanol or ethanol; A method comprising: [Section 2] Item 3. The process according to item 1, wherein the lower alcohol is a C1-C4 alcohol or a mixture of such alcohols, in particular methanol. [Section 3] Item 3. The method according to item 1 or 2, wherein the combined lithium hydroxide and lower alcohol of step (B) are mixed to obtain a suspension of particles in the lithium hydroxide solution. [Section 4] The crude lithium hydroxide provided in step (A) is Lithium hydroxide monohydrate containing 100 ppm to 1.29% calcium, 0.1 to 1.29% fluoride, and 0.1 to 1.29% sodium; or Anhydrous lithium hydroxide containing 175 ppm - 2.26% calcium, 0.175 - 2.26% fluoride, and 0.175 - 2.26% sodium and all amounts are by weight of dry solids. [Section 5] 5. The method according to any one of paragraphs 1 to 4, wherein the crude lithium hydroxide provided in step (A) further comprises one or more further impurities from the group of calcium salts, aluminum salts, zinc salts, the sum of calcium, aluminum and zinc typically amounting to an amount of such impurities of 100 ppm or more, based on the total weight of the crude lithium hydroxide solids. [Section 6] 6. The method of any one of claims 1 to 5, wherein 90% by weight of the crude lithium hydroxide solid provided in step (A) consists of anhydrous lithium hydroxide or lithium hydroxide monohydrate or a mixture thereof. [Section 7] 7. The method according to any one of items 1 to 6, wherein the crude lithium hydroxide provided in step (A) contains fluoride as an impurity in an amount of 500 ppm or more based on the total weight of the crude lithium hydroxide solid. [Section 8] The solution of lithium hydroxide obtained in step (B) is then (C) solid-liquid separation to obtain a clear solution; (D) optionally followed by the addition of water; (E) Drying, and (F) Isolation of lithium hydroxide solid as anhydrous, or as a monohydrate, or as a mixture of anhydrous and monohydrate, or as a mixture of the monohydrate with water and / or a lower alcohol, or as a mixture of the monohydrate with a lower alcohol, or as a mixture of the anhydrous and monohydrate with a lower alcohol. 8. The method according to any one of items 1 to 7, wherein the method is subjected to [Section 9] 9. The method of any one of paragraphs 1 to 8, wherein the combination of crude lithium hydroxide solids with a lower alcohol, such as methanol or ethanol, in step (B) contains less than 1 molar part of water per molar part of lithium, and in step (D) water is added in an amount of about 1 molar part of water per molar part of lithium or more. [Section 10] 10. The method according to any one of items 1 to 9, wherein the lithium hydroxide is further purified by an aqueous crystallization step, which is carried out before step (A) or after step (B), with subsequent removal of solids by solid-liquid separation (step C). [Section 11] 11. The method according to any one of items 1 to 10, wherein prior to step (A), the lithium hydroxide is further purified by adding sulfide ions or hydrogen sulfide ions to the aqueous solution of the crude lithium hydroxide. [Section 12] 12. The method according to any one of paragraphs 1 to 11, wherein the crude lithium hydroxide provided in step (A) is obtained from lithium ion battery scrap material after subsequent steps of reduction, optionally in the presence of an alkaline earth hydroxide, such as calcium hydroxide, aqueous leaching, separation of solids and drying. [Section 13] 13. The process according to any one of items 1 to 12, wherein the lower alcohol used is recovered by distillation or evaporation and recycled in the process. [Section 14] 1. A solid lithium hydroxide product comprising 1-100 ppm fluoride and 1-5000 ppm, particularly 1-3000 ppm, of non-volatile organic carbon, based on the total weight of the solid product. [Section 15] Item 15. A solid lithium hydroxide product according to item 14, comprising 1-100 ppm of fluoride and 1-1000 ppm, in particular 5-500 ppm, of a lower alcohol, such as methanol or ethanol, based on the total weight of the solid product.
Claims
1. A method for purifying lithium hydroxide from materials containing waste lithium ion batteries or parts thereof, comprising: (A) providing crude lithium hydroxide containing fluoride as a solid; (B) combining the crude lithium hydroxide provided in step (A) with a lower alcohol, which is a C1-C4 alcohol or a mixture of C1-C4 alcohols, and then mixing the combined lithium hydroxide and lower alcohol to obtain a suspension of solid particles in the lithium hydroxide solution; (C) separating the resulting solution containing dissolved lithium hydroxide from undissolved impurities by solid-liquid separation. A method comprising:
2. 2. The method of claim 1, wherein the lower alcohol is methanol or ethanol, or a mixture thereof.
3. The crude lithium hydroxide provided in step (A) is Lithium hydroxide monohydrate containing 100 ppm to 1.29% calcium, 0.1 to 1.29% fluoride, and 0.1 to 1.29% sodium; or Anhydrous lithium hydroxide containing 175 ppm to 2.26% calcium, 0.175 to 2.26% fluoride, and 0.175 to 2.26% sodium 3. The method of claim 1 or 2, wherein all amounts are by weight of dry solids.
4. 4. The process according to any one of claims 1 to 3, wherein the crude lithium hydroxide provided in step (A) further comprises one or more further impurities from the group of calcium salts, aluminium salts, zinc salts, the sum of calcium, aluminium and zinc amounting to an amount of 100 ppm or more, based on the total weight of the crude lithium hydroxide solid.
5. 5. The process of claim 1, wherein at least 90% by weight of the crude lithium hydroxide solids provided in step (A) consists of anhydrous lithium hydroxide or lithium hydroxide monohydrate or a mixture thereof.
6. 6. The process of claim 1, wherein the crude lithium hydroxide provided in step (A) comprises fluoride as an impurity in an amount of 500 ppm or more based on the total weight of the crude lithium hydroxide solids.
7. The solution of lithium hydroxide obtained in step (B) is then (C) solid-liquid separation to obtain a clear solution; (D) optionally followed by the addition of water; (E) Drying, and (F) Isolation of lithium hydroxide solid as anhydrous, or as a monohydrate, or as a mixture of anhydrous and monohydrate, or as a mixture of the monohydrate with water and / or a lower alcohol, or as a mixture of the monohydrate with a lower alcohol, or as a mixture of the anhydrous and monohydrate with a lower alcohol.
7. The method according to claim 1 , wherein the subjection is to
8. 8. The method of claim 7, wherein the combination of crude lithium hydroxide solids and lower alcohol in step (B) contains less than 1 mole of water per mole of lithium, and wherein water is added in an amount of 1 mole or more per mole of lithium in step (D).
9. 9. The method according to any one of claims 1 to 8, wherein the lithium hydroxide is further purified by a step of aqueous crystallization, which is carried out before step (A) or after step (B), with subsequent removal of solids by solid-liquid separation (step C).
10. 10. The process according to any one of claims 1 to 9, wherein prior to step (A), the lithium hydroxide is further purified by adding sulfide ions or hydrogen sulfide ions to an aqueous solution of the crude lithium hydroxide.
11. 11. The method according to any one of claims 1 to 10, wherein the crude lithium hydroxide provided in step (A) is obtained from lithium ion battery scrap material after sequentially carrying out the steps of reduction, aqueous leaching, solid separation and drying.
12. 12. The process according to any one of claims 1 to 11, wherein the lower alcohol used is recovered by distillation or evaporation and recycled in the process.
Citation Information
Patent Citations
Method for comprehensively recycling valuable metals from spent lithium ion battery
CN107017443A
Lithium battery material recovery method
JP1994251805A
Method for purifying lithium hydroxide
JP2012106874A
Method for separating and recovering valuable material from used lithium ion battery
JP2012229481A
Method of regenerating lithium precursor and recycling system of lithium precursor
KR101998691B1